Distribution of ABO Blood Group in Peptic Ulcer Patients in the Ethnic Population of Balochistan (Medical Forum Monthly, 2024)
Objective: To find relationship between ABO blood group and peptic ulcer (PU) in the ethnic population of Balochistan. Study Design: An observational and prospective study. Place and duration of Study: The study was carried at Bolan Medical College Complex Hospital Quetta for a period of one year. Patients and methods: 60 peptic ulcer patients confirmed with video endoscope were included. ABO blood group was determined by slide test method. Result: Out of 60 PU patients 54 were males and 6 females. 18 had blood group O, 24 had group B, 11 had AB and 7 had A blood group. 90% were Rhesus positive. O group was dominant (38.46%) in peptic ulcer patients with antral lesion. In patients having duodenal lesion, B group was prevalent (45.83%). Males were predominant sufferers (75%). The poor and middle class patients were equally affected. The ethnic group Pathan were more affected (36.67%) compared to Baloch and Hazara. Conclusion: Antral lesions are dominant in O blood group peptic ulcer patients whereas duodenal lesion is common in blood group B. There is a high prevalence in Pathan males. Duodenal lesion is more prevalent compared to antral lesion.